Gaetano Mosca — aktualność uwag o systemie demokracji przedstawicielskiej - Żyromski, Marek (Wydział Prawa i Administracji UAM, 1991)
The purpose of the article is to turn the readers' attention to the threats and dangers of functioning of the democratic system. The starting point for the considerations is the conception of a famous Italian sociologist Gaetano Mosca (1858-1941), a co-author of the sociological theory of elites. Gaetano Mosca was opposed to the introduction of a general right to vote and was against granting the voting rights to women. Besides, he was a strong opponent of proportional electoral regulations, and he stressed the role of electoral committees and the significance of a strong middle, class as a support for the democratic government. The article points to the topicality of some Mosca's views on the system of representative democracy. However, the article's main concern is to indicate some dangers for the emerging Polish democracy. In particular, the author points to: 1) the danger of indifference and weak political understanding among the Polish electorate; 2) the necessity to put forth alternative programmes (to make it possible to vote for particular programmes rather than for particular persons); 3) advantages and disadvantages of proportional and majority electoral regulations (the author is in favour of proportional regulations with a minimum threshold); 4) the necessity of reconstructing the middle class. Besides, the author stresses the dangers specific for the functioning of democracy at a local level. The topicality of many Gaetano's views on the functioning of democratic systems is the best proof of advantages flowing from the studies on the classical sociological thought.
Gaetano Mosca — topicality of remarks on the system of representative democracy